2019
DOI: 10.1111/ffe.12973
|View full text |Cite
|
Sign up to set email alerts
|

Strength and fatigue strength of a similar Ti‐6Al‐2Sn‐4Zr‐2Mo‐0.1Si linear friction welded joint

Abstract: Strengths for monotonic and cyclic loadings of similar overmatching Ti‐6Al‐2Sn‐4Zr‐2Mo‐0.1Si (Ti6242) linear friction welds (LFW) were studied and compared with the parent material (PM) behaviour. Non‐destructive synchrotron observations revealed the presence of pores in the weld interface. The weld centre zone (WCZ) showed a higher strength leading to lower macroscopic ductility of the cross‐weld samples. Local strain and normalized strain rate have been assessed by stereo digital image correlation (DIC) and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

7
22
0

Year Published

2019
2019
2025
2025

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 20 publications
(30 citation statements)
references
References 49 publications
(117 reference statements)
7
22
0
Order By: Relevance
“…Similarly, Dorick et al [46] reported intragranular precipitation of α' lathes in the weld center, which was transformed into acicular α+ β microstructure after the PWHT. Hardness results showed an increase of 27% hardness in the weld center compared with the base metal [45]. Also, TMAZ hardness values were slightly lower than the weld center hardness.…”
Section: Ti-6al-2sn-4zr-2momentioning
confidence: 87%
See 4 more Smart Citations
“…Similarly, Dorick et al [46] reported intragranular precipitation of α' lathes in the weld center, which was transformed into acicular α+ β microstructure after the PWHT. Hardness results showed an increase of 27% hardness in the weld center compared with the base metal [45]. Also, TMAZ hardness values were slightly lower than the weld center hardness.…”
Section: Ti-6al-2sn-4zr-2momentioning
confidence: 87%
“…Linear friction welding studies on Ti-6242 show comparable microstructural characteristics as reported in Ti-64 welds. A study conducted by García et al [45] on the strength and fatigue properties of LFW Ti-6242 showed that the weld center was composed of α' martensite, as shown in Figure 2-16. The TMAZ region was characterized by highly thermomechanically deformed grains oriented in the weld direction.…”
Section: Ti-6al-2sn-4zr-2momentioning
confidence: 98%
See 3 more Smart Citations